2013
DOI: 10.1192/bjp.203.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone-induced hypersexuality

Abstract: We report hypersexuality in three people with schizophrenia after starting risperidone, with evidence suggesting a possible link between risperidone and the hypersexuality. Mrs X, 71 years old, married once and widowed for 20 years, with no known history of hypersexuality, was started on risperidone 25 mg intramuscular (IM) injection three times weekly. Two months later, she complained of 'having to' masturbate two to three times daily without being able to orgasm, lactating and losing 'too much fluids' vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…ejakulierendes Verhalten führte [21]. Dies allerdings dazu kontrastierend, dass bei dem beschriebenen Fall einer Hypersexualität unter Risperidon der 5-HT 2A -Antagonismus dafür verantwortlich gemacht wird, dass die Hypersexualität aufgetreten ist, da durch den 5-HT 2A -Rezeptoren-Antagonismus die präfrontal erhöhte Dopaminausschüttung in die-sem Fall für die Hypersexualität verantwortlich gemacht wird [1]. Zusammenfassend scheint der in Anbetracht des wiederholt aufgetretenen pathologischen Spielens bzw.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…ejakulierendes Verhalten führte [21]. Dies allerdings dazu kontrastierend, dass bei dem beschriebenen Fall einer Hypersexualität unter Risperidon der 5-HT 2A -Antagonismus dafür verantwortlich gemacht wird, dass die Hypersexualität aufgetreten ist, da durch den 5-HT 2A -Rezeptoren-Antagonismus die präfrontal erhöhte Dopaminausschüttung in die-sem Fall für die Hypersexualität verantwortlich gemacht wird [1]. Zusammenfassend scheint der in Anbetracht des wiederholt aufgetretenen pathologischen Spielens bzw.…”
Section: Diskussionunclassified
“…Davidson et al berichten über Fälle von Hypersexualität, die durch Risperidon induziert wurden, bei einem 23-jährigen Mann, einem 53-jährigen Mann sowie einer 71 Jahre alten Frau. Sie vertreten dabei die These, dass der ausgeprägte 5-HT 2A -Rezeptoren-Antagonismus des Risperidon bezüglich der Hypersexualität eine kausale Rolle spielt in der Form, dass es bedingt dadurch zu einem Dopaminanstieg präfrontal kommen würde, zudem würde der Antagonismus am Alpha2-Rezeptor dazu führen, dass adrenerge Neuronen enthemmt werden, welche wiederum eine Rolle bei genitaler Stimulation spielen würden [1]. Gomez berichtet zudem über das Auftreten einer Hypersexualität bei 2 Männern im Alter von 25 und 28 Jahren, die Fluphenazindecanoat als Depotmedikament erhalten haben [2].…”
Section: Introductionunclassified
“…Secondary drug-induced hypersexuality, which is a well-established complication of dopamine-enhancing medications (e.g., antiparkinsonian drugs) (30,31), has also been associated with enhanced activation in similar regions, including the ventral striatum, cingulate, and orbitofrontal cortices (32). As only few clinical cases of SGA-induced hypersexuality have been reported in the medical literature, no evidence on neurobiological or imaging correlates of SGA-induced hypersexuality exists (10)(11)(12)(13)(14)(15)(16)(17). Nevertheless, an SGA-mediated increase in dopaminergic n e u r o t r a n s m i s s i o n , a b l o c k a d e o f s e r o t o n i n e r g i c neurotransmission or a combined effect, have been suggested as possible pathways for SGA-induced hypersexuality (17).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only very few cases of risperidoneinduced hypersexuality have been reported in the medical literature (16), while results from a randomized clinical trial showed less sexual dysfunction in patients treated with olanzapine compared to risperidone (38). Moreover, accumulating epidemiological evidence suggests that among the currently available antipsychotics, risperidone is the antipsychotic most frequently related to hyposexuality, amenorrhoea, and galactorrhoea, and is closely followed by haloperidol (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation